Beyond the Surface: Investigating Concealed Meanings in Drug Posters through Semiotic Analysis - Desak Putu Eka Pratiwi; I Komang Sulatra; I Made Andika Dwi Jaya (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Drug posters are intricate communicative artifacts that carry hidden connotations, myths, and ideologies. This article employs semiotic analysis to explore the layers of symbolism in these posters. By examining both verbal and visual signs, this study aims to uncover the connotative meanings embedded in drug posters and reveal the underlying myths and ideologies. Using Saussure's semiotic theory and Barthes' theory of meaning as frameworks, various drug posters were analyzed qualitatively. The findings highlight the complex interplay between verbal and visual signs, uncovering connotations, myths, and ideologies. This research enhances our understanding of the persuasive strategies in drug posters, offering insights into their socio-cultural impact. Verbal signs often conveyed warnings about the negative impacts of drug use, while visual signs reinforced these messages with additional layers of meaning